THU0611 Subjective Well-Being of Japanese RA Patients Who Reach Treatment Target Is Higher than The Japanese Average. (15th July 2016) - Kageyama, G.; Onishi, A.; Ueda, Y.; Kamei, Y.; Yamada, H.; Ichise, Y.; Waki, D.; Naka, I.; Tsuda, K.; Okano, T.; Takahashi, S.; Nishida, M.; et al.
Abstract : Background: Subjective Well-Being (SWB) refers to a construct which includes one's emotional responses, domain satisfactions, and global judgments of life satisfaction. Many variables such as age, sex, income, employment and marital status are related to SWB. Being healthy is also an important factor of SWB. RA is a chronic illness which is considered to influence SWB. However, little is known about the impact of RA on SWB. Objectives: To evaluate the SWB of Japanese RA patients and identify factors that associate with SWB. Methods: This study was done in cooperation with the Cabinet Office Government of Japan Economic and Social Research Institute. This institute had previously conducted the "Well-being studies 2014" surveying the SWB of randomly selected Japanese citizens. In this survey, SWB was determined by having the participants rate their happiness between 10 (Very happy) and 0 (very unhappy). The Well-being studies 2014 also included a questionnaire consisting of 56 questions covering topics closely associated with well-being such as socioeconomic and health status. The same survey was done for RA patients at Kobe University Hospital and clinical data including disease duration, stage, class, disease activity, HAQ, complications and the therapeutic drug was also collected at the same time. Results: Multivariate analysis on data including RA patients (n=339) and Japanese controls (n=7690) revealed that RA patients with high or moderate disease activity had similar SWB scores as Japanese controls. However, the SWB of RA patients with remission or low disease activity were higher than Japanese controls. Age, sex, marital status, presence of child, household income, financial leeway, working status, psychological distress (Kessler 6 scale), self-assessment of health, and social connection were all associated with SWB. Conclusions: Japanese RA patients may be able to get higher SWB than Japanese controls by achieving treatment target. Disclosure of Interest: None declared